2020
DOI: 10.1088/2053-1591/ab86f8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of mechanical properties for Mg-9Li-1Zn alloy by accumulative roll bonding

Abstract: The microstructures and mechanical properties of LZ91 alloys by accumulative roll bonding (ARB) were firstly investigated. The results show that the cycle numbers of ARB process and preheating temperatures before ARB process have an impact on the microstructures and mechanical properties of LZ91 alloys. The microstructures of LZ91 sheets after ARB perform two main phases of α and β in the fibrous form. ARB process can drive more numbers of crystallographic planes for α and β phases in LZ91 alloys to proof the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…19,20 Most of ARB was employed to refine the grains during Mg alloy rolling. [20][21][22] Saufan A et al 23 reported that 5 passes ARB was applied in Mg-9Li-1Zn which achieved grain refinement and strength increasing.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Most of ARB was employed to refine the grains during Mg alloy rolling. [20][21][22] Saufan A et al 23 reported that 5 passes ARB was applied in Mg-9Li-1Zn which achieved grain refinement and strength increasing.…”
Section: Introductionmentioning
confidence: 99%